2018
DOI: 10.1021/jacs.8b10370
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Bistability in Crystalline Organic Radicals: The Interplay of H-bonding, Pancake Bonding, and Electrostatics in 4-(2′-Benzimidazolyl)-1,2,3,5-dithiadiazolyl

Abstract: Figure 1. (top) Line drawing and labeled ORTEP plot of HbimDTDA (100 K; thermal ellipsoids at 50%); (bottom) singly occupied molecular orbital (SOMO) and electrostatic potential (ESP) surface calculated at uB3LYP/6-31G(d,p). Communication pubs.acs.org/JACS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 40 publications
1
51
0
Order By: Relevance
“…56,63 Such reversible phase transitions between different polymorphs in DTDA chemistry are extremely rare. 57,59,60,64 The observation of two single-crystal-to-single-crystal transitions between paramagnetic phases associated with 3β ↔3γ ↔ 3δ is almost unprecedented in DTDA chemistry. The successive breakdown in pancake bonding interactions in Preuss' Ln(hfac)3(boaDTDA)2 complex, perhaps provides the closest comparison (also two transitions) but a much more pronounced change in magnetic response since the latter is based around cleavage of the enthalpically favorable π * −π * pancake bond, switching from an S = 0 state to two S = ½ spins.…”
Section: Discussionmentioning
confidence: 99%
“…56,63 Such reversible phase transitions between different polymorphs in DTDA chemistry are extremely rare. 57,59,60,64 The observation of two single-crystal-to-single-crystal transitions between paramagnetic phases associated with 3β ↔3γ ↔ 3δ is almost unprecedented in DTDA chemistry. The successive breakdown in pancake bonding interactions in Preuss' Ln(hfac)3(boaDTDA)2 complex, perhaps provides the closest comparison (also two transitions) but a much more pronounced change in magnetic response since the latter is based around cleavage of the enthalpically favorable π * −π * pancake bond, switching from an S = 0 state to two S = ½ spins.…”
Section: Discussionmentioning
confidence: 99%
“…55 Other organic radicals exhibiting magnetic bistability include additional 1,3,2-dithiazolyls 33,56 , bis--1,2,3--dithiazolyls 57,58 , nitroxides 59 , spirobiphenalenyls 60,61 , and dithiadiazolyls. 62,63 The hysteresis loop of 1 is centered around 323 K and spans 46 K (see Figure 1, right). The different magnetic response of its two polymorphs (LT features diamagnetism, while HT features a weak paramagnetism 45 ) results from changes in the antiferromagnetic interactions between adjacent radicals along the π--stacks.…”
Section: Introductionmentioning
confidence: 99%
“…[83][84][85] Preuss et al found that radical 4-(2 0 -benzimidazolyl)-1,2,3,5-dithiadiazolyl (HbimDTDA) exhibits a first order phase transition around 270 K. The dense network of short contacts in HbimDTDA led to pancake bonds in LT diamagnetic phase and the breakage of pancake bonds (supramolecular interaction) in HT paramagnetic phase as clearly shown Review in the temperature varied crystal XRD analysis (Figures 10C and 10D). 86,87 Haddon et al observed that P3 exhibits three-physical-channel response: electrical, magnetic, and optical, simultaneously by changing the temperature around RT (Figures 10E and 10F). 18,88,89 Radical dimer P3 is paramagnetic and infrared (IR) transparent with s = 2.4 3 10 À2 S cm À1 at HT, which undergoes intramolecular electron switching and changes to diamagnetic, IR-opaque, and highly conductive state (1.4 3 10 À1 S cm À1 ) with decreasing temperature.…”
Section: Applications Multiple Channel Bistabilitymentioning
confidence: 98%
“…(C) Temperature dependence of paramagnetic susceptibility of HbimDTDA. (D) Crystal structures of HbimDTDA at 100 and 340 K. (Reprinted with permission from Preuss et al86 Copyright 2018 American Chemical Society). (E) Optical, electrical, and magnetic properties change with temperature.…”
mentioning
confidence: 99%